Growth of Jabon Seedling (Anthocephalus cadamba) on Medium of Ex-Sand Mining with the Addition of Sub Soil and Charcoal of Coconut Shell PERTUMBUHAN SEMAI JABON (Anthocephalus cadamba) PADA MEDIA BEKAS TAMBANG PASIR DENGAN PENAMBAHAN SUB SOIL DAN ARANG... - Basuki Wasis; Dadan Mulyana; Bayu Winata (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Sand mining is a natural resources exploitation. The effects of sand mining are environmental degradation and reduction of soil physical, chemical and biological quality. The land of ex-sand mining could be marginal land and constitutes a barrier for revegetation. Soil amendment is a necessary phase for overcoming this problem i.e. additional of sub soil and charcoal of coconut shell on the soil. Species selection also determines the success of revegetation. Jabon (Anthocephalus cadamba) is a pioneer, adaptive and fast growing species. The aims of this reasearch are to analyze the effects of sub soil and coconut shell charcoal addition on the growth of jabon seedlings on ex-sand mining soil, and to find out the optimum dose of sub soil and coconut shell charcoal addition. The results of this research showed that sub soil and coconut shell charcoal addition on ex-sand mining soil, increased the positive effect. The combination of 500 g of sub soil and 20 g of coconut shell charcoal gave the best growth for jabon seedling on ex-sand mining soil.Key words : Anthocephalus cadamba, charcoal, coconut shell, sand mining, sub soil.